PREPARING OF FUTURE MANAGERES OF EDUCATIONAL INSTITUTIONS TO DISTANCE LEARNING: PSYCHOLOGICAL AND ADMINISTRATIVE ASPECT - Ivanitska, Olga; Red’ko, Serhiy; Panchenko Allа (Continuing Professional Education: Theory and Practice, 2019)
The article is devoted to the preparing to distance learning of future school leaders, including the use of learning platform Moodle. As one of the basic tasks of higher education institutions that train specialists in administrative, managerial specialties, is training highly skilled and competitive specialist that is able to self-development and self-improvement according to the requirements European and global labor markets. That is why the need becomes actual for forming readiness to distance learning of students – future school leaders. This need defines the psychological readiness and ability to independent mastery for knowledge and skills to perform independent tasks learning in distance format. The formation of psychological readiness for distance education is one of the major tasks of professional training future managers in the education field, because it promotes independence, adequate self-esteem, the required level of harassment, internal motivation for independent learning and professional management activities. Psychological readiness of leaders to management is a complex of motives, knowledge and skills, personal qualities providing successful interaction the leader with the participants of the management process and management efficiency in general. In its structure, it is a complicated personal formation, which includes the following components: motivational, cognitive, operational, personal. The analysis of scientific sources allowed forming a model of psychological readiness of the future leaders of the educational field to distance learning. This model consists of motivational, professional and personal, cognitive, professionally and activity components. The motivational component expresses in need to achieve success in educational and professional managerial work. The professional and personal component provides the ability to self-awareness, self-esteem and self-regulation. The cognitive component detects the presence of a professional management knowledge and awareness of the essence of independent work. The professionally and activity component determines the self-improvement of the future manager’s personality. Distance learning is an activity that has a complex character. The subject of this training is the future manager of on the other educational institutions on one hand, provides training and manages this process on the other. Therefore, the readiness to distance learning should considered as a readiness for activities that in essence it is management. Any management activities bases on the project, which should develops according to the requirements of the result. In the case of distance learning, the main result is a master of future managers the new ways of actions for future management activity. They are derivatives from those professional tasks for which solution it is not enough already learned means. In other words, the project must be the project of a future leader’s changes. The assessment of readiness to distance learning is the expertise of this project.